Hysteroscopic polypectomy versus expectant management in endometrial polyps in asymptomatic infertile women: a meta-analysis - Modesto, Tauane Bahia; Dias, Amanda Tamiris Barbosa; de Oliveira, Sofia Andrade (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Endometrial polyp is a hyperplastic structural abnormality of the uterine cavity and is one of the most commonly found intrauterine abnormalities. The endometrial polyp is mostly asymptomatic and sometimes diagnosed only during infertility investigation. The influence of endometrial polyps on female infertility is not completely understood, however, due to the possibility of endometrial polyps influencing fertility, their removal is usually performed in women undergoing infertility treatment. Methods: This meta-analysis was performed through an electronic search using MEDLINE, PubMed in October 2017, bringing together the terms of interest in order to select studies that would compare polypectomy and expectant management for endometrial polyps in sub fertile women. Four articles were selected according to the inclusion and non-inclusion criteria. Results: Five variables were collected from the selected articles to be compiled and analyzed (rate of live births per transferred embryo, chemical pregnancy rate, spontaneous abortion rate, implantation rate and clinical pregnancy rate), none of which showed any difference statistically significant in conduct. Conclusions: The data concluded that there is no statistical significance between expectant management and polypectomy.